2009
DOI: 10.1521/jscp.2009.28.8.993
|View full text |Cite
|
Sign up to set email alerts
|

The Defensive Nature of Benefit Finding During Ongoing Terrorism: An Examination of a National Sample of Israeli Jews

Abstract: A study examining the effects of terrorism on a national sample of 1,136 Jewish adults was conducted in Israel via telephone surveys, during the Second Intifada. The relationship between reports of positive changes occurring subsequent to terrorism exposure (i.e., Benefit finding), posttraumatic stress disorder (PTSD) symptom severity, and negative outgroup attitudes toward Palestinian citizens of Israel (PCI) was examined. Benefit finding was related to greater PTSD symptom severity. Further, Benefit finding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 65 publications
(105 reference statements)
6
28
0
1
Order By: Relevance
“…Instruments had been used previously in Arabic with other Palestinian populations and found to have sound psychometric properties and construct validity (Hall, Hobfoll, Canetti Nisim, Johnson, & Galea, in press; Hobfoll et al, 2009; Hobfoll, Canetti-Nisim, Johnson, Palmieri, Varley, & Galea, 2008; Palmieri et al, 2008). Interviews were approximately 45 minutes in length.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instruments had been used previously in Arabic with other Palestinian populations and found to have sound psychometric properties and construct validity (Hall, Hobfoll, Canetti Nisim, Johnson, & Galea, in press; Hobfoll et al, 2009; Hobfoll, Canetti-Nisim, Johnson, Palmieri, Varley, & Galea, 2008; Palmieri et al, 2008). Interviews were approximately 45 minutes in length.…”
Section: Methodsmentioning
confidence: 99%
“…This scale has been used previously in studies of terrorism in Israel (Hobfoll et al, 2006, Hobfoll et al 2009; Hall et al, in press; Palmieri et al, 2008) among Arabs and Jews, and in the United States (Hobfoll, Tracy, & Galea, 2006) and was found to be predictive of PTSD. Participants were asked “To what extent have you lost any of the following things in the past year as a result of the occupation or violence among factions?” Sample items for interpersonal loss include: “Feeling that you are a person of great value to other people,” “stability of your family,” and “intimacy with at least one friend.” Examples of intrapersonal losses are: “the feeling that you are a successful person,” “Sense of control in your life,” and “Hope.” One additional item was used to assess loss of faith in the ability of the Palestinian governing authorities to protect participants’ family.…”
Section: Methodsmentioning
confidence: 99%
“…Cheng et al, 2006;Davis & McKearney, 2003;Frazier et al, 2009;Frazier & Kaler, 2006;Hall, Hobfoll, Canetti, Johnson & Galea, 2009;Hobfoll et al, 2007;McFarland & Buehler, 2012;McFarland & Alvaro, 2000;Wortman, 2004;Yanez, Stanton, Hoyt, Tennen & Lechner, 2011;Zoellner & Maercker, 2006). Most of these researchers do not question the existence of posttraumatic growth but the validity of selfreported posttraumatic growth.…”
Section: Theory Of Reports Of Constructive (Real) and Illusory Posttrmentioning
confidence: 99%
“…Other authors suggested that sometimes reports of posttraumatic growth are defensive in nature (e.g. Davis & McKearney, 2003;Hall, Hobfoll, Canetti, Johnson & Galea, 2009;Hobfoll et al, 2007;McFarland & Buehler, 2012). Here, potentially illusory reports of posttraumatic growth may be indicative of increased defensiveness where the affected person attempts to protect their self-structure against a mortality threat.…”
Section: Theory Of Reports Of Constructive (Real) and Illusory Posttrmentioning
confidence: 99%
“…Brief phone assessment of major depression (MD) relied on the 9-item Patient Health Questionnaire-9 (PHQ-9), a well-validated, highly sensitive instrument for identifying individuals with current MD (Kroenke, Spitzer, & Williams, 2001) used in Israeli Palestinian and Jewish populations (Hall, Hobfoll, Canetti–Nisim, Johnson, & Galea, 2009; Hall et al, 2010; Hobfoll, Canetti-Nisim, & Johnson, 2006; Hobfoll et al, 2008; Palmieri, Canetti-Nisim, Galea, Johnson, & Hobfoll, 2008) Items were rated on a 4-point likert scale (0 = not at all , 1 = several days , 2 = more than half the days , 3 = nearly every day ). To be classified as having MD consistent with DSM-IV-TR , (Association, 2000) participants had to endorse at least five symptoms of major depression, including depressed mood or a lack of interest or pleasure in activities for more than half of the days in the past two-weeks, and endorse impairment in their functioning at home or at work.…”
Section: Methodsmentioning
confidence: 99%